2017
DOI: 10.1128/jvi.02125-16
|View full text |Cite
|
Sign up to set email alerts
|

Mutations during the Adaptation of H9N2 Avian Influenza Virus to the Respiratory Epithelium of Pigs Enhance Sialic Acid Binding Activity and Virulence in Mice

Abstract: The natural reservoir for influenza viruses is waterfowl, and from there they succeeded in crossing the barrier to different mammalian species. We analyzed the adaptation of avian influenza viruses to a mammalian host by passaging an H9N2 strain three times in differentiated swine airway epithelial cells. Using precisioncut slices from the porcine lung to passage the parental virus, isolates from each of the three passages (P1 to P3) were characterized by assessing growth curves and ciliostatic effects. The on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…However, amino acid diversity at residue 180 of the HA protein could play an important role in zoonotic potential. Previously, we and others have shown that H9N2 viruses carrying the A180T/V substitution gain the ability to bind to human‐like receptor analogues (Sealy et al, ; Teng et al, ; Yang et al, ). The A180T/V substitution also enhances binding avidity towards avian‐like receptor analogues, which can attenuate virus replication in vitro ; however, the impact of this mutation in conjunction with a NA stalk deletion is currently unknown.…”
Section: Discussionmentioning
confidence: 94%
“…However, amino acid diversity at residue 180 of the HA protein could play an important role in zoonotic potential. Previously, we and others have shown that H9N2 viruses carrying the A180T/V substitution gain the ability to bind to human‐like receptor analogues (Sealy et al, ; Teng et al, ; Yang et al, ). The A180T/V substitution also enhances binding avidity towards avian‐like receptor analogues, which can attenuate virus replication in vitro ; however, the impact of this mutation in conjunction with a NA stalk deletion is currently unknown.…”
Section: Discussionmentioning
confidence: 94%
“…H9 IAVs do not seem to affect pigs, causing just mild respiratory signs. Most H9 isolates from pigs have been from farms in Hong Kong and China (Xu et al 2004;Cong et al 2007;Yu et al 2011a;Wang et al 2016b) and appear to be related to recurrent reintroductions rather than intraspecies circulation (Mancera Gracia et al 2017b;Yang et al 2017b). These observations are in line with experiments in pigs that show impaired transmission of H9N2 strains in pigs unless provided as reassortants in the background of swine-origin or human-origin IAV strains (Obadan et al 2015;Wang et al 2016b;Mancera Gracia et al 2017a,b;Yang et al 2017b).…”
Section: Clinical Signs Pathology and Interspecies Transmissionmentioning
confidence: 99%
“…To determine the virus release, 100 µL ALI medium was added at the respective time points to the apical compartment and incubated at 37°C. After 30 minutes, the apical medium was collected and used to determine the viral infectivity by endpoint dilution titration on MDCK cells as described previously [25].…”
Section: Virus Infectionmentioning
confidence: 99%